2014
DOI: 10.1007/s10909-014-1165-x
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Phase Transition in the Extended Three-Dimensional Falicov–Kimball Model

Abstract: We study the excitonic phase transition in a system of the conduction band electrons and valence band holes described by the three-dimensional (3D) extended Falicov-Kimball (EFKM) model with the tunable Coulomb interaction U between both species. By lowering the temperature, the electronhole system may become unstable with respect to the formation of the excitons, i.e, electron-hole pairs at temperature T = T∆, exhibiting a gap ∆ in the particle excitation spectrum. To this end we implement the functional inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(53 citation statements)
references
References 55 publications
3
50
0
Order By: Relevance
“…The e h − mass difference in the BCS-BEC transition scenario leads to a large suppression of the BEC transition temperature, which is proved to not be the same as the excitonic pair formation temperature [20,22,23]. This is in contrast with the previous treatments [5][6][7][8][9][10][11][12][13], where the EI state is associated with the BEC state of excitons, as to be identical.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…The e h − mass difference in the BCS-BEC transition scenario leads to a large suppression of the BEC transition temperature, which is proved to not be the same as the excitonic pair formation temperature [20,22,23]. This is in contrast with the previous treatments [5][6][7][8][9][10][11][12][13], where the EI state is associated with the BEC state of excitons, as to be identical.…”
Section: Introductionmentioning
confidence: 64%
“…(2) using the Hubbard-Stratonovich (HS) transformation [28]. We do not present here the calculation details [22,23] fter the HS linearisation, we got the total action of the system that is linear in terms of fermion density operators n rτ ( ) and n rτ( ).…”
Section: Hubbard-stratanovich Linearisationmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation is also typical for the double layer electronic structures at the half filling [21] when considering the electron-hole pair formation and condensation. In addition, it has been demonstrated that the excitonic insulator state and the excitonic condensation are two distinct phase transitions in the solid state [22,23], and the condensate states are due to the electronic phase stiffness [20,24], mechanism. Meanwhile, in the electronic bilayer systems, those mentioned phase transitions are indistinguishable as it was shown in references [12,21].…”
Section: Introductionmentioning
confidence: 99%